Project-based teaching and learning activities: a systematic review - Fefri Perrianty; Tri Haryati; Nova Berliana Yanti (STIKES Keluarga Bunda Jambi, 2021)
[Project-based teaching and learning activities: a systematic review]is a form of instruction that focuses on students based on 3 constructivist principles: teaching and learning activities are special conditions, students participate actively in teaching and learning activities and they achieve their mission through social interaction and provide insights and explanations. Cocco, 2006). It is considered as a type of teaching and learning activity with a special inquiry platform where the conditions for teaching and learning activities are carried out through authentic problems and problems in real world practice (Al -Balushi & Al - Aamri, 2014) which aim at meaningful learning experiences (Wurdinger, Haar , Hugg & Bezon , 2007). Blumenfeld, Fishman, Krajcik, Marx and Soloway (2000).